2007
DOI: 10.1093/rpd/ncm404
|View full text |Cite
|
Sign up to set email alerts
|

Determination of 226Ra in urine samples by alpha spectrometry

Abstract: A radiation protection system to assess the internal contamination of workers during decontamination activities in an abounded fertilizer industry in the region of Attika, Greece, has been implemented. This system concerns, among other radionuclides, 226Ra. Because of the low 226Ra activities in urine, alpha spectrometry was used as the determination method after radiochemical separation. Radium was co precipitated with lead sulphate and purified using anion and cation exchange techniques. The source for the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The system of protection for workers exposed to NORM is essentially the same as for workers exposed in other practices (Kehagia et al, 2007). As such, the principle of optimization and of control measures formed the basis of the radiation protection programme applied in this particular case.…”
Section: Radiation Protection Programmentioning
confidence: 99%
See 1 more Smart Citation
“…The system of protection for workers exposed to NORM is essentially the same as for workers exposed in other practices (Kehagia et al, 2007). As such, the principle of optimization and of control measures formed the basis of the radiation protection programme applied in this particular case.…”
Section: Radiation Protection Programmentioning
confidence: 99%
“…Since the first measurements performed for area characterization, it became obvious that there were two possible ways for workers exposure: external exposure and mainly internal exposure that could result from inhalation during mechanical operations, such as sawing, cutting, grinding and polishing of scale contaminated components. Based on gamma and alpha (Kehagia et al, 2007) spectrometric measurements of collected raw materials, such as sludge, dust and air filters, and taking into account parameters proposed in relevant EC Publications (RP 107, 1999), the initial estimation of the total effective dose to workers during the decontamination process, demonstrated that in any case it could not exceed 14 mSv. This value was the result of the worst-case inhalation scenario where the mean activity concentration for 226 Ra was 6000 Bq/kg and no protection measures were used.…”
Section: Radiation Protection Programmentioning
confidence: 99%
“…Alpha-particle spectroscopy is commonly used for applications in various fields such as nuclear [1][2][3][4], environmental [5][6][7][8], artistic [9,10], and biological [11][12][13][14] samples. Conventional approaches for the preparation of alpha-particle sources generally include (i) radiochemical separation and purification [15,16], (ii) preparation of weightless and thin solid source onto a suitable backing material [17][18][19], and (iii) alpha-particle spectroscopic measurements under vacuum conditions using solid-state semiconductor detectors [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical yields were 50-70%. [4] Dai et al reported a new rapid method for 226 Ra in urine using ion exchange resin. 224 Ra was used as a tracer, added with its parent 228 Th.…”
mentioning
confidence: 99%